Design and Implement of Staggered Parallel Lithium Battery Equalization Converter With Jumper Switches - Wang, Xueqi; Huang, Linlu; Chen, Guanhua; Li, Zexiang (Frontiers in Energy Research, 2022)
To mitigate the pressure on energy storage and enhance the flexibility of the power system, lithium-ion batteries are widely utilized in large-scale energy storage in smart grids due to their superior charging and discharging performance and energy storage characteristics. Whereas the inconsistency of lithium battery cells has become a key issue that limits the overall performance of the battery pack. A novel flexible equalization converter is proposed to handle this issue. This converter is combined with a staggered parallel topology and jumper switched, which enables an energy transfer path to exist between any cell to the rest pack and any substring to the rest substring. The electromagnetic transient model and its small-signal model of the proposed converter have been developed in MATLAB to prove its effectiveness. Finally, the conclusion could be arrived at that the proposed topology shows a better performance compared to the traditional method.